Founder Effects Contribute to the Population Genetic Structure of the Major Dermatophytosis Pathogen Trichophyton rubrum on Hainan Island, China - Geng Y; Wu W; Li R; Xu J; Gu R; Lu J; Zheng W; Zhao F; Zhang J; Gong J (Dove Medical Press, 2021)
Yuanyuan Geng,1,* Weiwei Wu,2,3,* Rouyu Li,4- 6 Juan Xu,1 Ruixue Gu,1 Jiejie Lu,2 Wenai Zheng,7 Fei Zhao,1 Jianzhong Zhang,1 Jie Gong1 1National Institute for Communicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing, People's Republic of China; 2Department of Dermatology, The Fifth People's Hospital of Hainan Province, Haikou, People's Republic of China; 3National Clinical Research Center for Skin and Immune Disease, Beijing, People's Republic of China; 4Department of Dermatology, Peking University First Hospital, Beijing, People's Republic of China; 5Beijing Key Laboratory of Molecular Diagnosis on Dermatoses, Beijing, People's Republic of China; 6Research Center for Medical Mycology, Peking University, Beijing, People's Republic of China; 7Department of Laboratory Medicine, The Fifth People's Hospital of Hainan Province, Haikou, People's Republic of China*These authors contributed equally to this workCorrespondence: Jie Gong Tel +86 10 5890 0368Email gongjie@icdc.cnBackground: Founder events have been observed among numerous plants and animal species living on oceanic islands due to the geographic separation of these islands and the small amount of original life they harbor. However, there has been little research on the ecological characteristics of pathogenic microorganisms on islands. Trichophyton rubrum ranks the most common isolated dermatophyte causing dermatophytosis in clinic and has become an epidemic strain worldwide in recent decades.Objective: To study the phylogenetic characteristics and the distribution pattern of genetic polymorphism of T. rubrum in China, which further provide theoretical basis for the prevention and control of T. rubrum.Methods: In the present study, we sequenced and analyzed the genetic characteristics of 204 T. rubrum isolates from Hainan Island and other sites in China. Phylogenetic analysis and genetic polymorphisms were studied based on a total of 41,409 high-quality whole-genome SNPs.Results: The majority of the isolates from Hainan Island clustered together. Mixed T. rubrum population differentiation was observed among the strains of different geographical origins. In addition, the genetic diversity (π) of the Hainan isolates was low and showed no significant difference from that of isolates from other sites.Conclusion: This study is the first to discuss general ecological and evolutionary principles related to pathogenic fungi. Our findings reveal a founder effect during the origination of T. rubrum on Hainan Island and provide guidance regarding prevention and treatment strategies.Keywords: founder effects, Trichophyton rubrum, genetic diversity, population differentiation